2020
DOI: 10.3390/plants9040413
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Comparative Analysis of MYB Transcription Factor Family in Musa acuminata and Musa balbisiana

Abstract: MYB transcription factors (TFs) make up one of the most important TF families in plants. These proteins play crucial roles in processes related to development, metabolism, and stimulus-response; however, very few studies have been reported for the characterization of MYB TFs from banana. The current study identified 305 and 251 MYB genes from Musa acuminata and Musa balbisiana, respectively. Comprehensive details of MYBs are reported in terms of gene structure, protein domain, chromosomal localization, phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…In a recent analysis RrMyb10 was reported as the anthocyanin inducer in Ribes species, and its role in manipulating anthocyanin biosynthesis in heterologous systems has been highlighted [ 186 ]. Also, recent comparative analysis and genome-wide identification of MYB TF s in two varieties of banana, Musa acuminata and Musa balbisiana would enable future prospects for functional studies [ 187 ]. Apart from these, SEPALLATA and SQUAMOSA class MADS BOX genes also regulate anthocyanin accumulation in fruits.…”
Section: Regulation Of Pigment Dynamics In Fruit Ripeningmentioning
confidence: 99%
“…In a recent analysis RrMyb10 was reported as the anthocyanin inducer in Ribes species, and its role in manipulating anthocyanin biosynthesis in heterologous systems has been highlighted [ 186 ]. Also, recent comparative analysis and genome-wide identification of MYB TF s in two varieties of banana, Musa acuminata and Musa balbisiana would enable future prospects for functional studies [ 187 ]. Apart from these, SEPALLATA and SQUAMOSA class MADS BOX genes also regulate anthocyanin accumulation in fruits.…”
Section: Regulation Of Pigment Dynamics In Fruit Ripeningmentioning
confidence: 99%
“…Presence of phylogenetic specific pattern of conserved domains has been reported by ( Azeem et al, 2018 , Waqas et al, 2019 ). This pattern of conserved motifs indicated the recent common origin of MYB TFs ( Du et al, 2013 , Tan et al, 2020 ). Furthermore, presence of conserved motifs supports the evidence of functional conservation and gene duplication events in plants ( Waqas et al, 2019 ).…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, presence of conserved motifs supports the evidence of functional conservation and gene duplication events in plants ( Waqas et al, 2019 ). Conserved motifs also determine the diversity of domain architecture which has been utilized to maintain beyond the core components of MYB domain and have an important role for the functioning of MYB related proteins ( Du et al, 2013 , Tan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous research, there are 64, and 223 MYB-related genes in the model plant Arabidopsis and rice, respectively (Chen et al, 2006(Chen et al, , 2019. Recently, 62 genes in Physcomitrella patens (Pu et al, 2020), 138 genes in Solanum tuberosum (Liu Y. H. et al, 2020), 73 genes in Musa acuminate, and 59 genes in Musa balbisiana (Tan et al, 2020) were identified as MYB-related genes. Plant MYB-related genes have been reported to be involved in multiple processes, including cellular and organ morphogenesis, secondary metabolism, circadian rhythm, and drought tolerance (Baldoni et al, 2015).…”
Section: Discussionmentioning
confidence: 99%